2012
DOI: 10.1248/bpb.35.164
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Capabilities of Tanshinone IIA against Cerebral Ischemia/Reperfusion Injury via Anti-apoptotic Pathway in Rats

Abstract: Danshen, derived from the dried root or rhizome of Salviae miltiorrhizae BGE., has Tanshinone IIA (TSA) as one of its active ingredients. Recent reports have shown that TSA can inhibit the apoptosis induced by serum withdrawal or ethanol in cultured PC12 cells. However, whether TSA has any neuroprotective effect remains unknown. In this study, we investigated the effects of TSA on cerebral apoptosis induced by middle cerebral artery occlusion (MCAO) in which cerebral ischemia had been induced 2 h earlier. Twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 30 publications
1
46
1
Order By: Relevance
“…The present results indicate that tanshinone IIA pretreatment normalizes markers of renal function, and reduced BUN and creatinine levels in the I/RIRI-induced rats. These findings are consistent with previous results demonstrating that tanshinone IIA attenuates hepatic (21) and cerebral ischemia/reperfusion injury (14). MPO primarily exists in the azurophilic granule of neutrophile granulocytes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present results indicate that tanshinone IIA pretreatment normalizes markers of renal function, and reduced BUN and creatinine levels in the I/RIRI-induced rats. These findings are consistent with previous results demonstrating that tanshinone IIA attenuates hepatic (21) and cerebral ischemia/reperfusion injury (14). MPO primarily exists in the azurophilic granule of neutrophile granulocytes.…”
Section: Discussionsupporting
confidence: 93%
“…In China, S. miltiorrhiza has been widely applied in the treatment of cardiovascular and cerebrovascular diseases (13). Tanshinone IIA is a key active monomer extracted from S. miltiorrhiza (14). Previous studies suggest that pre-treatment tanshinone IIA exerts a nerve protective effect against cerebral ischemia reperfusion injury (14,15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen and coworkers [37] showed that TSIIA treatment reduced the number of degenerated neurons, significantly (p < 0.05) increased the number of intact neurons, and inhibited cerebral apoptosis determined by TUNEL staining [37]. TSIIA decreased the expression of caspase-3 and caspase-8 and these results were proportional to the dose of TSIIA used [27].…”
Section: Tanshinone Iiamentioning
confidence: 99%
“…The structure of tanshinone IIA is shown in figure 7. Tanshinone IIA demonstrated an antiapoptotic effect via upregulating blc-2 expression and downregulating active caspase-3 in the cortex, subsequently reducing neural apoptosis, decreasing the brain infarct volume and attenuating neurological deficit in a rat MCAO model [207,208]. In addition, tanshinone IIA scavenged RNS in an ischemic stroke model [209].…”
Section: Active Compounds From Chinese Herbal Medicine For Targeting mentioning
confidence: 99%